Individual company and transformation of the entity (or the discussion on the pluripersonality of the legal person) - Pazos Hayashida, Javier (2017)
Starting off the critics to the general ideas about legal persons, especially in relation of his colective character, the article does a study about the rol of the Sole Proprietorship in the modern economic activity and the transformation of this entity.This is done by considering the needs and interests of the businessman, being that the option for one-person companies, or with many partners, is merely conjuctural. The social utility of the legal entity takes precedence over static considerations regarding the supposed “nature” of the institution.